Order Management and Supply Chain Performance of Motor Vehicle Assembly Firms in Kenya - Kiarie, Mary Njoki; Thogori, Miriam (International Journal of Supply Chain and Logistics, 2025)
Purpose: This study sought to establish the influence of order management on supply chain performance of motor vehicle assembly firms in Kenya. The study was premised on the order management theory. Methodology: The study adopted cross sectional survey design. The target population comprised the five (5) motor vehicle assembly firms in Kenya which are registered by Kenya Motor Industry (KAM, 2019). These firms are Isuzu East Africa Ltd (IEA), Associated Vehicle Assemblers (AVA), Kenya Vehicle Manufacturers (KVM), Trans Africa Ltd (TAL) and Mobius Motors Ltd. A total of 199 staff were selected from departments that engage in upstream and downstream supply chain activities in these firms. The sample size was determined using Slovin’s formula and stratified random sampling in the selection of 133 respondents from the target population. Primary data was collected using semi structured questionnaires. Prior to data collection, a pilot test was conducted to assess the validity and reliability of the research instruments. In the data processing and analysis, descriptive statistics was used and statistical output was generated using SPSS version 26. Inferential statistics was also used to infer correlation analysis as well as linear regression analysis. Findings: The study findings showed that order management had a positive and significant influence on the supply chain performance of motor vehicle assembly firms in Kenya. Motor vehicle assembly firms should streamline customer orders through automation of order management to improve accuracy and reduce delays. Further, improvement on the supply chain visibility is critical consideration in ensuring efficacy in ordering processes and combating shipment uncertainties through embracing supply chain agility practices. Unique Contribution to Theory, Practice and Policy: This study is anchored on order management theory that postulates the indispensable strategic relevance of order processing in motor vehicle assembly firms. It provides vital insights connecting capabilities, enabling mechanisms and supply chain performance outcomes to drive supply chain resilience and competitive advantage.